2013
DOI: 10.3732/ajb.1300018
|View full text |Cite
|
Sign up to set email alerts
|

Invasive congeners are unlikely to hybridize with native Hawaiian Bidens (Asteraceae)

Abstract: This result suggests that B. alba and B. pilosa are incapable of hybridizing with these Hawaiian Bidens taxa. Further, we found that B. alba in Hawaii was self-compatible, despite self-incompatibility throughout its native range, and that the tetraploid species B. alba and the hexaploid species B. pilosa were cross-compatible, although pollen fertility was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…Hawaiian Bidens (Carr 1987), in which low molecular variation is consistent with expectations of reduced genetic variation due to selfing, but might also be attributed to its recent and rapid origin (Helenurm and Ganders 1985;Knope et al 2012b;Knope et al 2013;Knope et al 2020a).…”
Section: Schenk Adaptive Radiations Of Plants 21mentioning
confidence: 52%
“…Hawaiian Bidens (Carr 1987), in which low molecular variation is consistent with expectations of reduced genetic variation due to selfing, but might also be attributed to its recent and rapid origin (Helenurm and Ganders 1985;Knope et al 2012b;Knope et al 2013;Knope et al 2020a).…”
Section: Schenk Adaptive Radiations Of Plants 21mentioning
confidence: 52%
“…Based on morphological and molecular (ISSR) data analysis, these authors concluded that low hybridogenic activity existed with B. frondosa. Knope et al (2013) also studied the hybridization between alien and native Bidens species. They hybridized B. alba and B. pilosa with nine native Hawaiian species and did not obtain viable hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…For radiations involving slowto-speciate taxa such as Hawaiian Metrosideros trees, the presence of multiple morphologically distinct yet weakly genetically diverged forms may result from the lack of persistent divergent selection on unstable volcanic islands (Stacy et al 2020) and species boundaries will likely disappear through introgression in this highly interfertile group. Likewise in Hawaiian Bidens, species are generally fully isolated either by geography (on different islands) and/or by habitat (and pollination syndrome for the one bird pollinated B. cosmoides on Kauai), but when secondary contact occurs the species can meld back together into hybrid swarms since intrinsic reproductive isolation has not yet occurred amongst any of the endemic Hawaiian species tested (Ganders and Nagata 1984;Knope et al 2013;Knope et al 2020). However, all Hawaiian species tested are intrinsically isolated, likely by genetic incompatibilities, from taxa in their hypothesized Central American sister clade (Knope et al 2013), and this reproductive incompatibility appears to have arisen within the past ~2 My (Knope et al 2012(Knope et al , 2020.…”
Section: Common Denominators Across Adaptive Radiations-questions and Answersmentioning
confidence: 99%